О формировании фауны птиц искусственных насаждений юга Украины за период с 1936 по 1967 г - Волчанецкин, И.Б.; Лисецкий, А.С.; Ходулях, Ю.К. (Вестник зоологии, 1970)
After many years of studying the formation of fauna in the artificial stands of the Ukraine and same regions of the RSFSR the ornitofauna of the artificial forest stands and field-protecting forest-belts was repeatedly examined in Kirovograd, Nikolaev, Kherson, Zaporozhie and Donetsk regions in June, 1966 and 1967. In the artificial stands of the Right-bank Ukraine there is no Emberiza melanncephala, which is met in the Left-bank area, and in the Left-bank area there are no Columba oenas, Bubo bubo, Sitta euro-paea, Phylloscopus collybitus, Ph.sibilator, Acanthopneuste trochiloides.
For the last period in artificial stands of the Right- and Left-bank Ukraine Phasianus colchicus was bred and, besides it, in the Left-bank Ukraine the following species were settled; Accipiter gentilis, A. nisus, Pernis apivorus, Corvus corax, Garrulus glandarius, Coccothraustes coccothraustes, Emberiza miliaria, Lullula arborea, Anthus trivialis, Fice-dula albicollis, Hippolais icterina, Turdus ericitorum, Merula merula, Phoenicurus phoeni-curus, Erithacus rubecula, Saxicola rubetra.
The settling of birds in artificial stands of the examined parts is shown in the table. The quantity of birds in some field-protecting forest-belts of the Left-bank Ukraine considerably increased. The settling of birds in the field-protecting forest-belts of the droughty steppes in Kherson region proceeds considerably worse even with artificial irrigation.